Can Living Donor Liver Transplantation in the United States Reach Its Potential?. Issue 11 (31st July 2021) - Kaplan, Alyson; Rosenblatt, Russell; Samstein, Benjamin; Brown, Robert S.
Abstract : Living donor liver transplantation (LDLT) is a vital tool to address the growing organ shortage in the United States caused by increasing numbers of patients diagnosed with end‐stage liver disease. LDLT still only makes up a very small proportion of all liver transplantations performed each year, but there are many innovations taking place in the field that may increase its acceptance among both transplant programs and patients. These innovations include ways to improve access to LDLT, such as through nondirected donation, paired exchange, transplant chains, transplant of ABO‐incompatible donors, and transplants in patients with high Model for End‐Stage Liver Disease scores. Surgical innovations, such as laparoscopic donor hepatectomy, robotic hepatectomy, and portal flow modulation, are also increasingly being implemented. Policy changes, including decreasing the financial burden associated with LDLT, may make it a more feasible option for a wider range of patients. Lastly, center‐level behavior, such as ensuring surgical expertise and providing culturally competent education, will help toward LDLT expansion. Although it is challenging to know which of these innovations will take hold, we are already seeing LDLT numbers improve within the past 2 years.